“THE CHINGANA WAS FAMOUS ...”. POPULAR ENTERTAINMENT AND NATIONAL CULTURE IN SANTIAGO DE CHILE, 1820 -1840. - Donoso Fritz, Karen (Revista de Historia Social y de las Mentalidades, 2011)
The “chinganas” were suburban sites of popular amusement strongly criticized by liberal and conservative elites, on account of the “immorality” practiced by their patrons. However, the “chinganero” atmosphere managed to penetrate the city center, invading theaters and coffee-houses with its characteristic dance, the “zamacueca”. The inf luence of these cultural forms was such that they became part of the national culture and the official celebrations, as the elite proved incapable of supplying its own cultural bases for its nation-building discourse. This national discourse was created by the elite to support and propagate its national project, but it was the popular traditions that gave it real content.